from the attachment, I have shown the following proof.
However, there's another part to this question which I'm having a little trouble with.
The question is as follows: Hence, show that ∇xE and ∇·E are both equal to zero at position P(x,y,z), unless x = y = z = 0. What happens at the origin?
I have tried working out ∇xE and ∇·E but I might be doing it the wrong way.
However, there's another part to this question which I'm having a little trouble with.
The question is as follows: Hence, show that ∇xE and ∇·E are both equal to zero at position P(x,y,z), unless x = y = z = 0. What happens at the origin?
I have tried working out ∇xE and ∇·E but I might be doing it the wrong way.
Attachments

31.4 KB Views: 2